A comparative study on the energy flow of a hybrid heavy truck between AMT and MT shift mode under local driving test cycle. (15th March 2022) - Feng, Renhua; Chen, Kunyang; Sun, Zhengwei; Hu, Xiulin; Li, Guanghua; Wang, Shaoyang; Deng, Banglin; Sun, Wangbing
Highlights: The energy flow of a hybrid heavy truck under AMT and MT Shift mode was experimentally investigated. The proportion of rear-axle work under MT shift mode is higher than that of AMT. The engine thermal efficiency under AMT and MT shift mode is 39% and 39.7%, respectively. The driving condition had a great influence on power units and key components. Abstract: In this study, the energy flow of a hybrid heavy truck between the AMT and MT shift modes under a local road driving cycle was experimentally investigated in a climate chamber. The energy flow distributions, specific drive mode, operating conditions, energy efficiency of the power system, and components in the AMT and MT shift modes were comparatively discussed in detail. Based on the experimental results, the average 100 km fuel consumption of local driving test cycle under AMT and MT shift mode was 46.17 L/100 km and 45.06 L/100 km, respectively. The local driving test cycle had a significant influence on the operating conditions of the power units and key components. Moreover, the proportion of rear-axle work that was used to drive the hybrid heavy truck under MT shift mode (35.62%) was higher than that of AMT (34.31%), primarily because under the MT shift mode, there is a higher recovered energy, higher motor mechanical efficiency, much more parallel dive time, and less engine direct drive time, leading to more economical engine operating points. The total effective thermal efficiencies of the engine under AMT and MT shift modes were 39% and 39.7%, respectively, and the recovered energies were 16425 kJ and 24893 kJ, respectively. The total mechanical efficiencies under the parallel drive mode of AMT and MT cycle modes were 94.2% and 95.3%, respectively, whereas those of under the energy recovery mode were 92.1% and 94.2%, respectively.